Hepatoprotective and Immunomodulatory Potential of ginger in Experimental Thioacetamide-Induced Liver Damage in mice. (Journal of the College of Basic Education, 2026)
Disorders of the liver are one of the top health-related public health issues facing the world today. Most liver conditions are caused by two main factors, namely oxidative stress and immune system dysfunction. Some of the most commonly used traditional medicinal plants that contain many beneficial chemical compounds include Zingiber officinale (Ginger) which is a rich source of two active compounds, gingerol, and shogaol. Traditionally used as an anti-inflammatory and antioxidant, this study evaluated the immunomodulatory and hepatoprotective effects of ginger in a rat model of thioacetamide (TAA)-induced liver injury. The rats were treated with ginger extracts (at doses of 200 and 400 mg/kg, and the effective dose was evaluated against silymarin, which is a standard hepatoprotective agent). Outcome measurements included changes in rat body weight and liver weight and serum liver enzymes (ALT, AST, ALP) that correlate with liver damage. Ginger treatment resulted in increased body weight, decreased liver weight, and restoration of the liver enzyme levels toward the normal range. Ginger at the higher dose (400 mg/kg) had hepatoprotective effects similar to silymarin.The hepatoprotective mechanism of ginger may be due to its antioxidant properties of free radical scavenging and immune modulation. In conclusion, Zingiber officinale is a potential candidate for both liver protection and immune system regulation, and through the integration of traditional methods with scientific evidence, ginger may also be considered an adjunct or alternative treatment for liver disease.